Effects of high fat diet on lipid accumulation, oxidative stress and autophagy in the liver of Chinese softshell turtle (Pelodiscus sinensis) - Zhong, Yiwen; Pan, Yaxiong; Liu, Li; Li, Honghui; Li, Yulong; Jiang, Jian; Xiang, Jing; Zhang, Jianshe; Chu, Wuying (Comparative Biochemistry and Physiology Part B: Biochemistry and Molecular Biology, 2020)
The present study was performed to determine the effect of high fat diet in lipid accumulation, oxidative stress and autophagy, and to explore the underlying molecular mechanism of high fat diet induced hepatic oxidative damage in Chinese softshell turtle. To this end, the control group were fed a normal fat diet (NFD, 6.38% lipid) and the experimental group were bred high fat diet (HFD, 13.89% lipid) for eight weeks. Lipid accumulation, oxidative stress and autophagy, as well as the mRNA expression of genes related to the antioxidant system were determined in the liver. Results showed that high fat diet not only exacerbated lipid accumulation in the liver and serum through increasing contents of triglyceride, total cholesterol and low-density lipoprotein and decreasing content of high-density lipoprotein, but also induced liver injury through increasing activities of alanine aminotransferase and aspartate aminotransferase in the serum. In addition, the experimental subject induced oxidative injury for the increase of reactive oxygen species, malondialdehyde and protein carbonyl contents and the reduction of glutathione contents, anti-superoxide anion capacity and catalase, total superoxide dismutase, glutathione peroxidase, glutathione-S transferase activities. Meanwhile, antioxidant-related signaling molecule expression were also decreased, which might attribute to regulate antioxidant-related signaling molecule. On top of that, it indicated promote the occurrence of liver autophagy via up-regulating expressions of AMP activated protein kinase, UNC-51-like kinase 1, Microtubule-associated proteins 1A/1B light chain 3 and down-regulating gene expression of mammalian target of rapamycin. In conclusion, high fat diet could enhance lipid accumulation in the liver and serum, lead to liver injury and oxidative damage, impair liver antioxidant capacity, regulate antioxidant-related signaling molecule expression and activate hepatic autophagy. [Display omitted] •High fat diet feeding induced lipid deposition and increased ROS level in the liver of Chinese softshell turtle;•The decreasing of enzyme activities and gene expression of antioxidant enzymes lead to oxidative stress.•Signaling molecules (Nrf2, Keap1, mTOR, S6K1) mediated the down-regulation of expression of antioxidant enzyme gene.•High fat diet feeding promote autophagy flux through inducing the expression of autophagy genes.